CFD Simulation and Experimental studying of a Dry Screw Vacuum Pump. Issue 1 (September 2021) - Ma, K; Guo, B; Zhou, Y; Wang, Y B
Abstract: Dry screw vacuum pumps are widely used in semiconductor, microelectronics and food industries due to their oil-free characteristics in the vacuum chamber during operation. The performance of screw vacuum pumps is usually predicted by one-dimensional numerical simulation or empirical methods. However, the above method cannot obtain the distribution of the fluid flow field inside the vacuum pump. In this paper, a three-dimensional model is established based on the experimental dry screw vacuum pump. The internal flow field of the dry screw vacuum pump was simulated by computational fluid dynamics (CFD) software using structured dynamic grid. The flow characteristics of the fluid inside the vacuum pump were analyzed. The distribution of the pressure field and velocity field inside the compressor is obtained. Comparing the P-θ indicator diagram and the performance parameters of the vacuum pump with the experimental results. It was found that the results of the three-dimensional numerical simulation were more consistent with the trends of the experimental data. On this basis, the flow field characteristics and performance of the vacuum pump are analyzed and the flow field of the vacuum pump can be better understood.